2010
DOI: 10.3109/00365510903518191
|View full text |Cite
|
Sign up to set email alerts
|

Plasma YKL-40 and recovery of left ventricular function after acute myocardial infarction

Abstract: Plasma YKL-40 was significantly increased in STEMI patients at admission and G-CSF treatment caused a further increase in YKL-40. Plasma YKL-40 may be an indirect marker of LVEF recovery, independent of hs-CRP, and higher plasma YKL-40 indicates a lower recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 31 publications
0
19
1
Order By: Relevance
“…In a large study in 72 patients with acute MI treated with primary PCI plasma YKL-40 and HsCRP were measured on day 1, 3, 7 and 30 (Hedegaard et al 2010). Plasma YKL-40 was significantly increased in MI patients (median 92 g/l) at baseline compared to 234 healthy subjects (median 34 g/l) and decreased to normal levels 30 days after treatment.…”
Section: Acute Myocardial Infarction and Ykl-40mentioning
confidence: 98%
See 1 more Smart Citation
“…In a large study in 72 patients with acute MI treated with primary PCI plasma YKL-40 and HsCRP were measured on day 1, 3, 7 and 30 (Hedegaard et al 2010). Plasma YKL-40 was significantly increased in MI patients (median 92 g/l) at baseline compared to 234 healthy subjects (median 34 g/l) and decreased to normal levels 30 days after treatment.…”
Section: Acute Myocardial Infarction and Ykl-40mentioning
confidence: 98%
“…Macrophages in atherosclerotic plaques express YKL-40, and the highest expression was found in macrophages in early atherosclerotic lesions (Rehli et al 2003;Boot et al 1999). Recent studies have demonstrated that serum YKL-40 is increased in patients with acute myocardial infarction (MI) (Nojgaard et al 2008;Wang et al 2008;Hedegaard et al 2010) and in patients with stable chronic CAD (Wang et al 2008;Kastrup et al 2009;Kucur et al 2007;Rathcke et al 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that serum YKL-40 is increased in patients with acute myocardial infarction (MI) [11,19,20] and in patients with stable chronic CAD [5,7,8,11]. Serum YKL-40 can be elevated sevenfold around the time of a MI and decreases slowly thereafter [11,19,20]. YKL-40 may also be an indirect marker of poor left ventricular recovery after a MI [19] and is correlated to the number of diseased coronary arteries [8].…”
Section: Introductionmentioning
confidence: 99%
“…Serum YKL-40 can be elevated sevenfold around the time of a MI and decreases slowly thereafter [11,19,20]. YKL-40 may also be an indirect marker of poor left ventricular recovery after a MI [19] and is correlated to the number of diseased coronary arteries [8]. Furthermore, in a population of 4,372 patients with stable chronic CAD, serum YKL-40 was a strong marker for the risk of cardiovascular death and total death within a 2.6 year follow-up period [7].…”
Section: Introductionmentioning
confidence: 99%
“…One study showed a negative correlation between maximal Ch3l1 levels and left ventricular EF recovery after MI. In patients receiving granulocyte-colony stimulating factor treatment there was an increase in plasma Ch3l1 but no correlation with cardiac recovery [15]. Patients suffering from MI often have several co-morbidities and are in a state of chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%